A Switched-DC Source Sub-Module Multilevel Inverter Topology for Renewable Energy Source Applications - Mohammad Ali Hosseinzadeh; Maryam Sarebanzadeh; Ebrahim Babaei; Marco Rivera; Patrick Wheeler (IEEE Access, 2021)
This article presents a sub-module topology for switched DC source cascaded multilevel inverter configurations that require fewer switching devices and can generate a high number of voltage levels that are suitable for renewable energy sources. The proposed sub-module topology comprises eight semiconductor switches and four DC voltage sources that generate fifteen voltage levels. Furthermore, the cascaded topology is presented to increase the output voltage levels and to minimize the number of components. The proposed sub-module inverter and its cascaded topology are compared with several multilevel inverters to indicate the advantages and drawbacks of the proposal. The comparison studies show that the proposed topologies require fewer switching devices and gate drivers in comparison with other multilevel inverter topologies. In addition, the proposed cascaded topology reduces the cost of the inverter when compared to other multilevel inverter configurations. Furthermore, the power loss calculations and the implementation of the proposed topology in grid-connected photovoltaic applications are simulated and analyzed. Finally, the performance of the proposal is verified by simulation and experimental results for both symmetric and asymmetric sub-module topologies as well as for the proposed cascaded topology.